من أسلمة جاوى إلى أجوية الإسلام - Zainul Maarif (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2023)
Abstract Sunan Kalijaga was one of Islamic propagators in Nusantara (now Indonesia) since the end of Majapahit Kingdom era until the rise of Islamic Mataram Kingdom. By synergizing Javanese culture and Islamic religion, Sunan Kalijaga was the driving figure of Islamizing Java and Javanizing Islam. His acculturation produces clement religion and culture that held by majority of Nusantara people massively. Remembering the harmony of religion and culture can build a better world, this article contains a study of Sunan Kalijaga’s acculturation model. Firstly, it reveals Sunan Kalijaga’s personality and ideas concerning synthesizing Islam and Javanese. After interpreting examples of Sunan Kalijaga’s acculturation, this paper identifies and explain the characteristics of his acculturation, to inspire acculturation efforts in other places andtimes. Key Words: Sunan Kalijaga, Acculturation, Religion, Culture, Islam, Javanese Abstrak Sunan Kalijaga adalah salah seorang penyeru agama Islam di Nusantara (Indonesia sekarang) sejak akhir masa Kerajaan Majapahit hingga kemunculan Kerajaan Mataram Islam. Dengan menyinergikan kebudayaan Jawa dan agama Islam, Sunan Kalijaga merupakan figur pendorong Islamisasi Jawa dan Jawanisasi Islam. Akulturasinya memproduksi agama dan budaya yang sejuk dan dianut oleh mayoritas orang Nusantara secara massif. Mengingat harmoni antara agama dan budaya bisa membentuk dunia yang lebih baik, tulisan ini berisi kajian tentang model akulturasi yang digagas Sunan Kalijaga. Yang pertama diungkap adalah kepribadiaan dan ide-idenya mengenai sintesisasi Islam dan Jawa. Setelah menginterpretasikan contoh-contoh akulturasi Sunan Kalijaga, tulisan ini mengidentifikasi dan menjelaskan karakteristiknya, demi menginspirasi upaya akulturasi di tempat dan waktu berbeda. Kata Kunci : Sunan Kalijaga, Akulturasi, Agama, Budaya, Islam, Jawa ملخص سونان كاليجاغا هو أحد دعاة الإسلام في نوسانتارا (Nusantara) (إندونيسيا الآن) منذ نهاية مملكة ماجاباهيت (Majapahit) حتى ظهور مملكة ماتارام (Islamic Mataram). من خلال التآزر بين الثقافة الجاوية والدين الإسلامي، كان سونان كاليجاغا شخصية دافعة لأسلمة جاوى (أي جعْل جاوى إسلاماً) وأجوية الإسلام ( أي جعْل الإسلام جاوياً). ينتج تثاقفه دينا ثقافيا معتدلا اعتنقه معظم سكان نوسانتارا أفواجا. باعتبار امكانية بناء عالم أفضل من الانسجام بين الدين والثقافة، تحتوي هذه الكتابة على نموذج التثاقف لسونان كاليجاغا. تكشف أولا عن شخصية سونان كاليجاغا وأفكاره المتعلقة بتوليف الإسلام وجاوى. بعد تفسير نماذج من تثاقف عند سونان كاليجاغا، تحدد وتشرح هذه الورقة خصائصه لإلهام جهود التثاقف في أماكن وأوقات أخرى. الكلمات الأساسية :سونان كاليجاغا، التثاقف، الدين، الثقافة، الإسلام، جاوى